Cotas raciais como política de admissão UERJ, UnB e o caso da UFG - GALVÃO, Eduardo Aires Berbert (2009)
The brazilian s public universities have choosen some unusual ways to admit new students like bonus, social quota and racial quota. UERJ and UnB were pioneers to adopt this unusual method. As a result of that many studies were built including this alternative admission ways. Therefore most of all studies are on racial quota. As a rule, if the study s goal is to critic the racial quota it needs to ignore the theorical reference about affirmative actions. On the other hand, if it doesn t do that, it will be impossible to proceed this critic because racial quota would appear as a real and good university passport possibility. This work inoves because it tries to do a critic about racial quota without ignore the theorical reference produceed about affirmative actions. We started from classics themes of sociology (democracy, citizenship and social justice), which are the origins of affirmative actions in the field. We purpose affirmative actions as a continuum from the classics themes mentioned above, so we can discuss affirmative actions as a public policies to promote individual s recognition. From this perspective we can do a critic about racial quote like recognition politicies based on identity model and suggest an alternative, based on status model. Based on the assumption above, we try to compare affirmative action program of UERJ and UnB, as well to verify the UFG s forward in your affirmative actions program.